2019
DOI: 10.4314/ahs.v19i1.57
|View full text |Cite
|
Sign up to set email alerts
|

Oral parafunctions, personality traits, anxiety and their association with signs and symptoms of temporomandibular disorders in the adolescents

Abstract: Objectives To investigate the association between oral parafunctions, personality traits, anxiety and signs and symptoms of temporomandibular disorders in the adolescents. Methods Two hundred and seventy adolescents were examined clinically for the signs and symptoms of temporomandibular disorders. Participants completed questionnaires about demographic variables, medical history, symptoms of temporomandibular disorders, parafunctional oral habits, Minnesota Multibasic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
3
30
2
3
Order By: Relevance
“…Winocur et al 55 found that biting hard objects and nail biting were associated with tired jaws in adolescent females. Atsü demonstrated that TMD signs and symptoms were relatively more frequent in the adolescent female group (47.8%), and these results may be explained by biological differences, hormone levels and higher pain sensitivity in women 59 . In the present study, the effects of gender, age, place of residence, and education level on the OBC score were observed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Winocur et al 55 found that biting hard objects and nail biting were associated with tired jaws in adolescent females. Atsü demonstrated that TMD signs and symptoms were relatively more frequent in the adolescent female group (47.8%), and these results may be explained by biological differences, hormone levels and higher pain sensitivity in women 59 . In the present study, the effects of gender, age, place of residence, and education level on the OBC score were observed.…”
Section: Discussionmentioning
confidence: 93%
“…Bruxism is the most common oral motor activity and is anticipated to be present in 31% of the general population 58 . Nail biting and holding objects in the mouth are other oral parafunctions observed frequently in children and adolescents 59 . Winocur et al 55 found that biting hard objects and nail biting were associated with tired jaws in adolescent females.…”
Section: Discussionmentioning
confidence: 99%
“…Oral habits or parafunctions are described as habitual functions that involve masticatory system and are not physiologically justified (Atsü, Güner, Palulu, Bulut, & Kürkçüoglu, 2019; Emodi‐Perlman et al., 2012). Oral habits are just like stress neither uncommon nor always harmful.…”
Section: Introductionmentioning
confidence: 99%
“…We conclude this rich menu of papers with what one would call a mixed salad: effect of oral contraceptives on periodontal health56; mental health and temporomandibular disorders57; and end with the reliability and validity of the patient activation measure PAM58.…”
mentioning
confidence: 95%